A brief history of time - Hawking, S. W. (Stephen W.) (New York : Bantam Books, 1998)
Provides an introduction to today's scientific ideas about the cosmos and reviews past theories. Also covers black holes, quarks, antimatter, and other mysteries of physics.
Includes index.
Publisher's Weekly.
Wilson's Public Library.
Wilson's Senior High School.
Young Adult
Keywords: Cosmology; Cosmology